The function of communities in protein interaction networks at multiple scales - Lewis, A; Jones, N; Porter, M; Deane, C (2010)
If biology is modular then clusters, or communities, of proteins derived using only protein interaction network structure should define protein modules with similar biological roles. We investigate the link between biological modules and network communities in yeast and its relationship to the scale at which we probe the network.